Analisis Anggaran Pelaksanaan Pemilihan Walikota Solok Pada Pilkada Serentak Nasional Tahun 2015 - Hendri Koeswara; Ira Irawati; Arry Bainus (Pusjar SKPP Lembaga Administrasi Negara, 2018)
The Solok Mayor Election was one of the simultaneous Election of Regional Heads held on the first wave of national elections along with 269 regions in Indonesia and simultaneously with the Governor Election and 13 Regents/Mayors in West Sumatera Province. Not only the simultaneous implementation of Pilkada but the joint funding was initiated to reduce the burden of the regional budget. The research which aims to explain the process of budgeting of Solok Mayor Election in the first wave regional elections in year 2015. Using qualitative research method with a case study approach, this study concludes that the Solok Mayor Election budget has been based on the principles in the budget preparation stage and formulation in the budget cycle. Turbulence policy on the implementation of the election model in the Election of Regional Heads is anticipated with policy anticipation both in terms of planning and budgeting that it doeas not disrupt the regional budget cycle. But on the other hand, there is no proportional joint funding (cost sharing) according to the workload among the executors of the Simultanoeus Regional Head Election that it makes the budget for the Election of Regional Heads burden for the Solok City Regional Revenue Budget Keywords: Budgeting, budget, simultaneously local elections Abstrak Tulisan ini tentang analisis anggaran pelaksanaan Pemilihan Walikota Solok Tahun 2015yang termasuk dalam Pilkada serentak nasional gelombang pertama di Indonesia bersama 269 daerah dan serentak dengan Pemilihan Gubernur serta 13 Bupati/Walikota di Provinsi Sumatera Barat. Tidak saja pelaksanaan Pilkadayang serentak tetapi pendanaan bersama kembali digagas untuk mengurangi beban anggaran daerah. Riset yang bertujuan untuk menjelaskan proses penganggaran Pemilihan Walikota Solok pada Pilkada Serentak Nasional Gelombang Pertama pada Tahun 2015 yang lalu. Tulisan ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus dalam penelitian. Sehingga dapat disimpulkan bahwa anggaran Pemilihan Walikota Solok telah berdasarkan pada prinsip-prinsip dalam tahapan budget preparation and formulation dalam siklus anggaran. Turbulensi kebijakan tentang pelaksanaan model pemilihan dalam Pilkada diantisipasi dengan kesiapan kebijakan (policy anticipation) baik dari sisi perencanaan maupun anggaran sehingga tidak mengganggu siklus anggaran daerah. Tapi, disisi lain tidak terjadi pendanaan bersama yang proporsional (cost sharing) sesuai beban kerja diantara pelaksana Pilkada serentak sehingga menjadikan anggaran Pilkada beban bagi APBD Kota Solok Kata Kunci : Penganggaran, anggaran, pilkada serentak